Solving the microheterogeneity of Bothrops asper myotoxin-II by high-resolution mass spectrometry: insights into C-terminal region variability in Lys49-phospholipase A2 homologs - Lomonte, Bruno (2022)
Myotoxin-II, a phospholipase A2 (PLA2)-like protein found in Bothrops asper venom, causes rapid necrosis of muscle fibers in spite of lacking enzymatic activity. This toxic action maps to its C-terminal region, within a segment known as “115–129” (consensus numbering) that displays a combination of cationic and hydrophobic amino acids, capable of destabilizing membranes. Although myotoxin-II is found in B. asper from both the Caribbean and Pacific regions of Costa Rica, this work shows that in the latter, position 124 is occupied by phenylalanine, instead of leucine reported for the Caribbean variant (UniProt P24605), thus solving the ambiguity described in the original sequencing of this toxin. A comparative inspection of sequences in the C-terminal region of 70 PLA2-like proteins showed that, with few exceptions, position 124 is occupied by either leucine or phenylalanine with equal frequencies. In line with earlier observations on primary and three-dimensional structural data, this comparison supports the notion that the disruptive mechanism of PLA2-like myotoxins toward membranes is not dependent on a fixed amino acid sequence motif across members of this subfamily, but instead on a spatial array of physicochemical properties which can be provided by variable combinations of cationic and hydrophobic residues. This plasticity bears resemblance to features of many antimicrobial peptides acting upon membranes. From a practical point of view, it is recommended to define the identity of the many isoforms of PLA2s and PLA2-like proteins found in viperid venoms by relying on the accurate determination of their intact mass, as these proteins are not known to present post-translational modifications.